LED pumped micron-scale all-silicon Raman amplifier. (October 2017) - Datta, Tanmoy; Sen, Mrinal
Abstract: A micron-scale all-silicon Raman amplifier has been proposed in this paper, exploiting the giant Raman gain of silicon nanocrystal material along with the extreme optical confinement of slotted photonic crystal waveguide. Light Emitting Diode (LED) has been considered here for low-cost optical pumping and the possibility of on-chip integration. At the same time, LED pumping eradicates the temporal impairment of output pulses which is otherwise unavoidable in case of continuous wave laser pumping. An overall gain of 3.22 dB has been achieved for a 400 Gbps input pulse train with a waveguide length of the amplifier which is as small as 4 μm. Moreover, the strong electroluminescence of silicon nanocrystal opens up the possibility of integrating the pump source on the same platform and, hence, expedites the future scope of realizing micron-scale silicon Raman laser without external pump source. Highlights: A highly integrable LED pumped all-silicon Raman amplifier has been proposed. The model is based on Si nanocrystal embedded slotted photonic crystal waveguide. LED pumping eradicates the Raman induced temporal impairment of output pulses. The design explores integration the pump source on the same platform. Realizing μm-scale Si Raman laser without external pump becomes promising future.